(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda holds a prominent and exceptional place in Indian scientific heritage. Ayurveda places a strong emphasis on prevention and aids in promoting and extending a happy, healthy life. Chikitsa in Ayurveda is the result of diligent effort and judicious use of Chatushpada (Four pillars of treatment). Bhaishajya kalpana is an important branch of Ayurveda which mainly deals with the development of diverse Ayurvedic formulations. Panchavidha Kashaya Kalpana is the basic five therapeutic preparations. Varti Kalpana is a unique Ayurvedic dosage form and it is an Upakalpana of Kalka Kalpana mentioned in Panchavidha kashaya kalpana. Its mode of action and administration is different from Vati Kalpana even though it has similar physical structure and method of preparation. Bruhatrayees were extensively explains about different types of Varti like Netra Varti, Guda Varti, Yoni Varti etc. Siras, Basthi and Hrudayam are collectively called as Trimarma and Guda is one among the Maha marma. Diseases of these vital parts can be safely managed with Varti prayoga without causing any complications. Varti prayoga is included in Stanika chikitsa (local treatment) but it can impart local as well as systemic effect. Manasiladi Dhumavarti indicated in Kasa, Kayastyadi Varti and Yashtyadi Varti in Apasmara, Sallakadi dhumavarti in Unmada are the examples of Varti prayoga which exert systemic effect. The convenience of Varti is enhanced by its simple administration, quick response, and user-friendliness.